Kontribusi Self Control terhadap Ketergantungan Gadget pada Anak di Sekolah Nurul Hasaniah - Hutasuhut, Dina Hidayati; Yarshal, Dinda (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Gadgets are one of the results of technological developments that have sophisticated capabilities, where the wider community cannot be separated from one group of gadget users. This research aims to determine self-control of gadget dependence among Nurul Hasanah students in the 2023/2024 academic year. The method used in this research is a quantitative method. This type of research is Quasi-experimental with a Pre test-post test one group design type. The subjects in this research were 6 students in class VIII-3 who had high gadget dependency scores. The instrument used is the gadget dependency scale. Instruments were given before and after the implementation of group counseling services. The data were analyzed using the Wilcoxon test to see whether there was an effect of providing self-control technique group counseling services on student gadget dependence. This was obtained from the results of calculations with the initial test score (pre-test) in the experimental group obtained an average of = 102.14 while the post-test data obtained an average of = 66.36. The results of this research can be obtained from the Wilcoxon test which shows that in the Wilcoxon test obtained J count = 9 while J table = 0. From the table of critical values J for the Wilcoxon test is marked with the power n=6, α= 0.05 in accordance with the acceptance and rejection criteria hypothesis then the hypothesis is accepted if Jcount > Jtable, namely Jcount>Jtable where 9 > 0, from this calculation it can be seen that the treatment in the experimental group means the hypothesis states that there is a significant influence of providing group counseling services on self-control techniques on gadget dependence in class VIII students - 3 at Nurul Hasaniah School Medan for the 2023/2024 academic year can be accepted.